2009
DOI: 10.1111/j.1365-2699.2007.01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐lethal entanglement of humpback whales (Megaptera novaeangliae) in fishing gear in northern Southeast Alaska

Abstract: Aim Entanglement in fishing gear is recognized as a potentially significant source of serious injury and mortality for humpback whales (Megaptera novaeangliae) in some parts of their range. In recent years, the number of humpback whales reported to have been entangled in Alaska has increased. In 2003-04 we quantified the prevalence of non-lethal entanglements of humpback whales in northern Southeast Alaska (SEAK) with the ultimate goal of informing management discussions of the entanglement issue for the Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 19 publications
(40 reference statements)
2
66
0
2
Order By: Relevance
“…A study of humpback whales in the North Atlantic found 64.9% of the population to have entanglement scarring when first assessed in 2003 and acquiring new scarring at an average annual rate of 12.1% (Robbins 2009). A study of humpback whales off southeast Alaska found 71% of that population to have entanglement scarring, with an annual acquisition rate of 8% between 2002 and 2003 (Neilson et al 2009). Other species of large whales also experience entanglement (Read et al 2006; see NOAA Stock Assessment Reports at www.nmfs.noaa.gov/pr/sars/), but there are relatively few studies with sufficiently detailed photo-identification data to assess population-wide and annual rates of entanglement.…”
Section: Discussionmentioning
confidence: 99%
“…A study of humpback whales in the North Atlantic found 64.9% of the population to have entanglement scarring when first assessed in 2003 and acquiring new scarring at an average annual rate of 12.1% (Robbins 2009). A study of humpback whales off southeast Alaska found 71% of that population to have entanglement scarring, with an annual acquisition rate of 8% between 2002 and 2003 (Neilson et al 2009). Other species of large whales also experience entanglement (Read et al 2006; see NOAA Stock Assessment Reports at www.nmfs.noaa.gov/pr/sars/), but there are relatively few studies with sufficiently detailed photo-identification data to assess population-wide and annual rates of entanglement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ingestion, entanglement in fishing gear can also result in death [16]. Studies of entanglement are usually based on necropsies or scarring [10] [16], but there are a few that have examined the impact of entanglement on cetacean behavior [17] [15] [18]. Virtually no studies have detailed behavioral changes based on observations of individuals before, during, and after entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Drift nets are estimated to kill thousands of dolphins (Delphinus delphis, Stenella coeruleoalba) in the Mediterranean each year [9]. The majority of humpback whales (Megaptera novaeangliae) in near-shore waters of northern Southeast Alaska bear scars of non-lethal entanglement [10]. Fishing gear entanglement is the leading cause of death for large whales in the Northwest Atlantic [11], and is one of the greatest threats to the critically endangered Mediterranean monk seal [12].…”
Section: Introductionmentioning
confidence: 99%
“…Debris collected from other North Sea coastlines such as Germany, the Netherlands, Belgium, France, Norway and Denmark, has been largely attributed to shipping and fishing activity (Galgani et al, 2000;van Franecker et al, 2005;Vauck and Schrey, 1987). Furthermore, fishing gear, operational as well as floating fragments, has been shown to cause entangling and mortality of marine animals (Derraik, 2002) including seabirds (Bugoni et al, 2008;Simeone et al, 1999;Stempniewicz, 1994;Votier et al, 2011;Zador et al, 2008), cetaceans (Johnson et al, 2005;Neilson et al, 2009;Ramos et al, 2011;Robbins and Matilla, 2004), turtles (Carr, 1987), sharks (Sazima et al, 2002) and seals (Hanni and Pyle, 2000;Hofmeyr et al, 2006;Page et al, 2004).…”
Section: The Fishing Industry As a Source Of Marine Debris On Beachesmentioning
confidence: 99%